O contexto agroecológico dos agricultores familiares e suas percepções no núcleo Oeste do Paraná da Rede Ecovida: perspectivas, avanços e desafios - Engelmann, Mara Irene (2018)
The debate on sustainability and more sustainable ways of dealing with the environment in which we live have permeated with relevant importance in the rural environment. Regarding this theme, the present dissertation presents an approach regarding the dynamics of agroecological production of the farmers members of the West Center of Paraná of the Ecovida Network of Agroecology. Through the method of participant observation and the application of a questionnaire in an interview, the data were obtained, making possible the subsequent analysis of the same. Through the farmers' perceptions, it was possible to analyze important aspects related to the agroecological production and agroecology in the region studied. The results obtained show a growing agro-ecological scenario, which faces some obstacles, with the challenge of overcoming social problems, such as lack of labor, family succession, lack of adequate technologies, financial support, access to agroecological inputs, as well as the low organization of farmers in access to markets. Farmers find prospects for progress in the technical support of non-governmental organizations such as Biolabore and also the important support of Itaipu Binacional, which is a reference in encouraging sustainable practices and has been doing a relevant job with rural producers in the western region of Paraná, promoting the strengthening of non-conventional Family Agriculture. In the face of the recent and progressive discourse on sustainability, it is clear that the work of agroecological farmers becomes important and of great relevance for part of the society that seeks a rural with another development perspective, that of sustainable development.